Normative data for the Visual Span test: evolutionary study of visual working memory and verbal working memory (European Journal of Education and Psychology, 2012)
The main purpose of this study was the standardization of a test for the assessment of visual working memory in a large sample of children from elementary grades. In addition, we analyzed the development of verbal and visual working memory within a context of cross-sectional design. We selected a sample of 1.030 children aged between 6 years and 3 months to 12 years and 4 months attending elementary school from 1rst to sixth grade. We administered the Visual Span of the Wechsler Memory Scale III, forward and backward, for visual working memory, and Memory for Phrases Test of Siegel y Ryan for verbal working memory. The results show a progressive improvement as a function of age in the performance of children for both tests. We also show tables of means, standard deviations and percentiles for different age groups. These standardized data may be used by professionals interested in the assessment of executive functioning of child school population.